Use of Blockchain Technology in Implementing Information System Security On Education - Agung Rizky; Sandira Kurniawan; Rizky Dwi Gumelar; Viki Andriyan; Muhammad Bian Prakoso (Program Studi Pendidikan Biologi, 2021)
Utilizing blockchain technology for information system security in the field of education is that all information data that has been entered cannot be faked, lost, or damaged easily, and also with blockchain, one can send data and information instantaneously and be decentralized without relying on third parties. Blockchain is a ledger that can efficiently and effectively record transactions between two parties that have been distributed and in a verifiable and permanent way. However, even though the application of blockchain technology in education has not been utilized globally However, researchers try to evaluate the security of information systems in education using fingerprints by implementing cryptographic hash security sensors so that the results of this study are achieved and are useful for the world of education. This research method uses the SWOT method and all these things will be discussed.Keyword : Blockchain Technology, Education, Swot Method